2023
DOI: 10.1038/s41598-023-31750-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of burden among caregivers of older emergency department patients

Abstract: The number of older individuals that live independently at home is rising. These older individuals often rely on caregivers who have a similar age and health status. Therefore, caregivers may experience a high burden. We determined the prevalence and associating factors of burden among caregivers of older patients in the emergency department (ED). A cross-sectional study of primary caregivers of patients aged ≥ 70 years visiting the ED of a Dutch teaching hospital was performed. Structured interviews were cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In the Mexican population of OAs that we studied, the prevalence of dependence in terms of activities of daily living measured through the Katz Index was like that reported in other studies [ 29 , 30 , 31 , 32 , 33 ]. It is known that during an acute health problem, OAs can become dependent, increase their level of dependency, or even lose their functional independence.…”
Section: Discussionsupporting
confidence: 73%
“…In the Mexican population of OAs that we studied, the prevalence of dependence in terms of activities of daily living measured through the Katz Index was like that reported in other studies [ 29 , 30 , 31 , 32 , 33 ]. It is known that during an acute health problem, OAs can become dependent, increase their level of dependency, or even lose their functional independence.…”
Section: Discussionsupporting
confidence: 73%
“… 103 Prior studies have found about a third of caregivers of older adults in the EDs are experiencing a high caregiver burden. 104 If there is concern for intentional abuse or neglect, Adult Protective Services or a long‐term care ombudsman should be alerted by ED staff. Integration of a vulnerable elder team or validated screening tool for elder mistreatment increases identification and assists with getting services for these patients.…”
Section: Transition Of Carementioning
confidence: 99%
“…However, this solution only works for those with caregiver support. In one study based in the Netherlands, having a primary caregiver was reported in 32% of older adults who visited the emergency department [ 22 ]. This figure may be slightly lower in Canada.…”
Section: A Website That Assesses Frailty Is Restrictive To the Frailmentioning
confidence: 99%